Transmission of the polymorphic dorsal pattern of the Iberian painted frog Discoglossus galganoi is compatible with simple Mendelian inheritance - F. J. Zamora-Camacho (Animal Biodiversity and Conservation)
To understand the evolutionary processes involved in the expression of ecologically relevant phenotypical variability it is necessary to disentangle the processes that govern the heredity of said traits. Such is the case of dorsal patterns in the Iberian painted frog, Discoglossus galganoi, which presents both a striped and a spotted morph. Here I studied whether the expression of such patterns is subjected to single-locus Mendelian heredity. I crossed males and females with each pattern in all possible combinations and calculated the percentage of each pattern in the offspring. The proportions obtained were compatible with single-locus Mendelian heredity.